1988
DOI: 10.1128/mcb.8.10.4185
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of ethyl methanesulfonate-induced reversion of a chromosomally integrated mutant shuttle vector gene in mammalian cells.

Abstract: The molecular mechanisms of ethyl methanesulfonate-induced reversion in mammalian cells were studied by using as a target a gpt gene that was integrated chromosomally as part of a shuttle vector. Murine cells containing mutant gpt genes with single base changes were mutagenized with ethyl methanesulfonate, and revertant colonies were isolated. Ethyl methanesulfonate failed to increase the frequency of revertants for cell lines with mutant gpt genes carrying GC--AT transitions or AT-*TA transversions, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Furthermore, the properties of the revertants described above suggest that reversion could be used to efficiently analyze the specificity of base changes induced by various mutagens. Indeed, our studies on EtMesinduced reversion reveal a very high degree of specificity for the types of mutations that are revertible by EtMes and for the type of base change observed in the revertants (19). By choosing an appropriate panel of mutants (i.e., those that revert primarily by a specific type of base change after mutagenesis) to test for reversion induced by mutagen treatment, it should be possible to use mammalian cells to determine the mutagenic specificity of various agents.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the properties of the revertants described above suggest that reversion could be used to efficiently analyze the specificity of base changes induced by various mutagens. Indeed, our studies on EtMesinduced reversion reveal a very high degree of specificity for the types of mutations that are revertible by EtMes and for the type of base change observed in the revertants (19). By choosing an appropriate panel of mutants (i.e., those that revert primarily by a specific type of base change after mutagenesis) to test for reversion induced by mutagen treatment, it should be possible to use mammalian cells to determine the mutagenic specificity of various agents.…”
Section: Methodsmentioning
confidence: 78%
“…With respect to mutagen treatment, it is important to note that the reversion assay could be much more sensitive than the forward mutation assay. We have recently shown that EtMes can increase reversion in this system by approximately 1000-fold above the spontaneous level (19). In contrast, we had found that EtMes increased forward mutation in A912 cells by only 10-fold (3).…”
Section: Methodsmentioning
confidence: 95%
“…The DNA sequences associated with the possible GPTI revertants of each cell line are also presented in Table 1. Revertant lines possessing each of the possible revertant DNA sequences presented have been isolated in previous studies from this laboratory (22,32,33). For lines B12 and B20, reversion has been observed to occur only by a G'C -* A-T transition at the site of the original mutation and restoring the wild-type DNA sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The latter type reversion events result in nonwild-type revertant DNA sequences. Thus, based on the types of reversion events that have been observed with lines S1, S44, B12, and B20, the sequences associated with these lines make it possible to use reversion analysis to assess thymidine mutagenesis at the 5' and 3' guanine residues of a Mutant sequences and all observed revertant sequences (21,32,33) GG doublet, the middle guanine residue of a GGG triplet, and the 3' guanine residue of a GGGG quartet.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of a particular base change that restores a wild-type DNA sequence can be measured by the frequency of phenotypic revertants, permitting the collection of large amounts of data about molecular events in the absence of marker recovery and DNA sequencing. An assay measuring phenotypic reversion of a bacterial transgene within mouse cells has been described, but determination of the molecular basis of reversion entailed both transgene recovery and sequencing, since second-site reversion was observed and no readily assayed markers for molecular events were described (8,25). Since this report describes mutation at a specific nucleotide pair, one cannot generalize from these data about the frequency at which the same mutations might occur at other sites.…”
mentioning
confidence: 99%